Pengaruh Content Marketing, Brand Ambassador dan Harga Pada Keputusan Pembelian Produk Skincare pria BROMEN - Aisyah Reza Pahlevi; Hasan Ubaidillah; Rifdah Abadiyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of content marketing on consumer purchasing decisions for product X. Content marketing, as a strategy based on delivering relevant and valuable content, has increasingly become a key factor in building consumer engagement and influencing buying behavior. This research employs a quantitative approach using a survey method involving 150 respondents who are active social media users and consumers of product X. The data were analyzed using multiple linear regression to examine the impact of content marketing variables—namely content relevance, content consistency, content quality, and content engagement—on purchasing decisions. The results show that content marketing significantly influences consumer purchasing decisions when considered simultaneously. Partially, the variables of content relevance and content engagement have the most dominant influence compared to the other variables. These findings indicate that delivering content that is relevant to consumer needs and interactive in nature can enhance trust and buying interest. This study provides practical implications for business practitioners to strengthen their content marketing strategies by focusing on relevance and engagement to drive purchasing decisions.